Genetic suppression of a dnaG mutation in Escherichia coli. - Katayama, T (1989)
Escherichia coli strains with a temperature-sensitive mutation, dnaG2903, in the primase-encoding gene spontaneously reverted to the temperature-insensitive phenotype at a high frequency. Many of the reversions were caused by extragenic sdg suppressors. About 100 independently isolated sdg suppressors were analyzed. They fall into two classes. The sdgA mutations were genetically mapped very close to and upstream of the dnaG gene and were found to be cis dominant. DNA sequencing of two of them revealed that G----A and C----A base substitutions had occurred 43 and 62 bases, respectively, upstream of the dnaG start codon. This region represents a transcriptional terminator thought to contribute to control of dnaG gene expression. The other class of suppressor, sdgB, seemed to comprise mutant alleles in the rpoB gene coding for the beta subunit of RNA polymerase core enzyme. Some of them were initially isolated as rifampin-resistant mutants. Both the sdgA and sdgB suppressors were found to increase the transcriptional activity of dnaG. This finding and other observations led to the proposition that sdgA and sdgB suppress the phenotype caused by dnaG2903 by overproducing the mutated primase; the quantitative oversupply may compensate for the qualitative defect of the dnaG2903 primase. An alternative mechanism of suppression by sdgB is discussed.